2009
DOI: 10.1128/jb.01767-08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TenBrucellaGenomes Reveals Evidence for Horizontal Gene Transfer Despite a Preferred Intracellular Lifestyle

Abstract: The facultative intracellular bacterial pathogen Brucella infects a wide range of warm-blooded land and marine vertebrates and causes brucellosis. Currently, there are nine recognized Brucella species based on host preferences and phenotypic differences. The availability of 10 different genomes consisting of two chromosomes and representing six of the species allowed for a detailed comparison among themselves and relatives in the order Rhizobiales. Phylogenomic analysis of ortholog families shows limited diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
108
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 56 publications
11
108
0
1
Order By: Relevance
“…83_13. Clustering within the classical Brucella species was similar to that of other studies (Wattam et al, 2009;Whatmore et al, 2014), demonstrating the close proximity of B. canis to B. suis bv. 4 and the separate position of B. suis bv.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…83_13. Clustering within the classical Brucella species was similar to that of other studies (Wattam et al, 2009;Whatmore et al, 2014), demonstrating the close proximity of B. canis to B. suis bv. 4 and the separate position of B. suis bv.…”
supporting
confidence: 75%
“…Although genome similarities of these potential novel species of Brucella are still above 90 % compared with classical species (Wattam et al, 2009;this study), the majority of these novel candidates carries genetic information not found in classical species but similar to genetic information found in other soil-living bacteria, such as Ochrobactrum, Paracoccus denitrificans, Agrobacterium and Sinorhizobium. This suggests a different ecology and extended exchange of genetic material via horizontal gene transfer and/or loss of genetic information and genome reduction in the classical Brucella species.…”
mentioning
confidence: 99%
“…abortus 9-941 ( Halling et al, 2005), B. suis ( Paulsen et al, 2002), B. canis ( Wattam et al, 2009), B.…”
Section: Introductionunclassified
“…ovis ( Wattam et al, 2009), Brucella sp. 83/13 (Broad Institute of MIT and Harvard, Cambridge, USA, http://www.broad.mit.edu/annotation/genome/brucella_group/GenomeDescriptions.html#Brucella_sp_ 83_13_v1), and B. microti CCM 4915 ( Audic et al, 2009) revealed various differences within these species.…”
Section: Introductionmentioning
confidence: 99%
“…The Bartonella genus is composed of 24 species sharing a core genome and subdivided based on phylogenomic analysis in four phylogenetic lineages, lineage 1 being the most ancestral lineage with Bartonella bacilliformis as sole species (Saenz et al 2007;Engel and Dehio 2009;Engel et al 2011). The Brucella genus includes 10 species defined according to their preferential host and divided, based on phylogenomic analysis, in four clades: Brucella abortus -Brucella melitensis, Brucella suis -Brucella canis, Brucella ovis, and Brucella ceti (Wattam et al 2009), with Brucella ovis being a potential common ancestor (Foster et al 2009). …”
Section: Bartonella and Brucella: Closely Related Pathogens With Distmentioning
confidence: 99%